Systematic Literature Review: Bagaimana Cara Meningkatkan Kemampuan Komunikasi Matematis Siswa - Noperta Noperta; Maila Sari (Universitas Dr. Soetomo, 2026)
Abstract Students’ low mathematical communication skills pose a challenge in 21st-century mathematics education. This study aims to explore applicable methods for improving students’ mathematical communication skills in mathematics education through a systematic literature review (SLR). The study was conducted according to the PRISMA guidelines. Data were retrieved using Publish or Perish and Google Scholar with the keyword “mathematical communication skills,” yielding 654 articles. The articles were then screened based on inclusion criteria, resulting in 93 final articles for analysis. Data were analyzed using thematic synthesis to categorize the methods or approaches for improving students' mathematical communication skills. The results of the study indicate that there are five categories for improving students’ mathematical communication skills: constructivist models, cooperative learning, problem-based approaches, technology-based learning, and metacognitive or scaffolding. The dominant criterion used was constructivist models, with 35 articles. In particular, the models most commonly used are CTL and RME. This study recommends that mathematics teachers integrate one of the five criteria into their instructional design. Furthermore, future research could conduct qualitative explorations involving broader and more in-depth studies to uncover how students’ mathematical communication skills improve, as well as develop a wider variety of assessment tools beyond written tests.. Keywords: Learning Mathematics, Mathematical Communication skills, Systematic Literature Review Abstrak Rendahnya kemampuan komunikasi matematis siswa menjadi tantangan dalam pembelajaran matematika abad ke-21. Penelitian ini bertujuan untuk mengeksplorasi cara yang dapat diaplikasikan untuk meningkatkan kemampuan komunikasi matematis siswa dalam pembelajaran matematika melalui metode systematic literature review (SLR). Penelitian dilakukan berdasarkan prosesedur PRISMA, pencarian data menggunakan bantuan publish or perish dan Google Cendikia dengan kata kunci kemampuan komunikasi matematis yang dihasilkan sebanyak 654 artikel. Kdemudian artikel diseleksi berdasarkan kriteria inklusi hingga diperoleh 93 artikel final untuk dianalisis. Data dianalisis menggunakan teknik thematic synthesis untuk mengkategorikan metode atau cara meningkatkan kemampuan komunikasi matematis siswa yang didapatkan. Hasil penelitian menunjukkan terdapat 5 kategori untuk meningkatkan kemampuan komunikasi matematis siswa, yaitu constuctivist models, cooperative learning, problem based approaches, technology based learning, dan metacognitive atau scaffolding. Kriteria yang dominan digunakan constuctivist models yaitu sebanyak 35 artikel. Sedangkan, model-model secara spesifik yang bayak digunakan adalah CTL dan RME. Penelitian ini menyarankan agar guru matematika mengintegrasikan salah satu dari lima kriteria ke dalam desain pembelajaran. Selain itu, untuk penelitian selanjutnya dapat melakukan eksplorasi kualitatif yang melibatkan penelitian secara global dan lebih mendalam untuk mengungkap bagaimana proses peningkatan komunikasi matematis siswa, serta pengembangan instrumen asesmen yang lebih variatif di luar tes tulis. Kata Kunci: Kemampuan Komunikasi Matematis, Pembelajaran Matematika, Systematic Literature Review